Implementing an Evidence-Based Intervention for Children in Europe: Evaluating the Full-Transfer Approach. (29th March 2019) - Sigmarsdóttir, Margrét; Forgatch, Marion S.; Guðmundsdóttir, Edda Vikar; Thorlacius, Örnólfur; Svendsen, Gøye Thorn; Tjaden, Jolle; Gewirtz, Abigail H.
Abstract : This study evaluated the implementation outcomes of GenerationPMTO, an evidence-based parenting intervention for child and adolescent behavior problems, in three European countries. The implementation approach was full transfer, in which purveyors train a first generation (G1) of practitioners; adopting sites assume oversight, training, certification, and fidelity assessment for subsequent generations (Forgatch & DeGarmo, 2011; Forgatch & Gewirtz, 2017). Three hundred therapists participated in trainings in GenerationPMTO in Iceland, Denmark, and the Netherlands. Data are from the implementation's initiation in each country through 2016, resulting in 6 generations in Iceland, 8 in Denmark, and 4 in the Netherlands. Therapist fidelity was measured at certification with an observation-based tool, the Fidelity of Implementation Rating System (Knutson, Forgatch, Rains, & Sigmarsdóttir, 2009). Candidates in all generations achieved fidelity scores at or above the required standard. Certification fidelity scores were evaluated for G1 candidates, who were trained by the purveyor, and subsequent generations trained by the adopting implementation site. In each country, certification fidelity scores declined for G2 candidates compared with G1 and recovered to G1 levels for subsequent generations, partially replicating findings from a previous Norwegian study (Forgatch & DeGarmo, 2011). Recovery to G1 levels of fidelity scores was obtained in Iceland and the Netherlands by G3; in Denmark, the recovery was obtained by G5. The mean percentage of certification in each country was more than 80%; approximately 70% of certified therapists remained active in 2017. Findings support full transfer as an effective implementation approach with long-term sustainability and fidelity.